Mr, Pengembangan LKPD Berbantuan Komik Matematika Menggunakan Model Guide Inquiry untuk memfasilitasi Literasi Matematis: LKPD berbantuan komik matematika pada Materi Statistika Kelas VII Menggunakan Model Guided Inquiry - Ahmad Saipul Rokhim; Sugeng Sutiarso; Undang Rosidin (Mandalika Mathematics and Educations Journal, 2026)
This study aims to develop mathematics comic-assisted teaching materials using the Guided Inquiry learning model to facilitate students’ mathematical literacy skills on the topic of Statistics for seventh-grade students at SMP Adab Kesuma Bangsa. The background of this research stems from the low level of students’ mathematical literacy, as indicated by their difficulties in understanding contextual problems, interpreting data, and connecting mathematical concepts to real-life situations. The research employed a Research and Development (R&D) method with the ADDIE development model, consisting of the stages of Analyze, Design, Develop, Implement, and Evaluate. The validation results by material experts obtained a score of 0.81 categorized as “very valid,” while media experts obtained a score of 0.82 also categorized as “very valid.” The practicality test showed a student response score of 0.87 and a teacher response score of 0.88, both in the “very practical” category. The effectiveness of the teaching material was tested using a t-test with a significance value of <0.05, indicating a difference in the average mathematical literacy ability between the experimental and control classes. Thus, the developed mathematics comic-assisted teaching material is declared valid, practical, and effective in facilitating students’ mathematical literacy skills and can serve as an innovative alternative in mathematics learning at the junior high school level.